Prenatal Exposure to a Maternal High Fat Diet Increases Hepatic Cholesterol Accumulation in Intrauterine Growth Restricted Rats in Part Through MicroRNA-122 Inhibition of Cyp7a1 - Zinkhan, Erin K.; Yu, Baifeng; Schlegel, Amnon (Frontiers in Physiology, 2018)
Intrauterine growth restriction (IUGR) and consumption of a high saturated fat diet (HFD) increase the risk of hypercholesterolemia, a leading cause of morbidity and mortality. The mechanism through which the cumulative impact of IUGR and in utero exposure to a maternal HFD increase cholesterol levels remains unknown. Cholesterol 7α hydroxylase (Cyp7a1) initiates catabolism of cholesterol to bile acids for elimination from the body, and is regulated by microRNA-122 (miR-122). We hypothesized that IUGR rats exposed to a maternal HFD would have increased cholesterol and decreased Cyp7a1 protein levels in juvenile rats, findings which would be normalized by administration of a miR-122 inhibitor. To test our hypothesis we used a rat model of surgically induced IUGR and fed the dams a regular diet or a HFD from prior to conception through lactation. At the time of weaning, IUGR female rats exposed to a maternal HFD had increased hepatic cholesterol, decreased hepatic Cyp7a1 protein and hepatic bile acids, and increased hepatic miR-122 compared to non-IUGR rats exposed to the same HFD. In vivo inhibition of miR-122 increased hepatic Cyp7a1 protein and decreased hepatic cholesterol. Our findings suggest that IUGR combined with a maternal HFD decreased cholesterol catabolism to bile acids, in part, via miR-122 inhibition of Cyp7a1.